A new species of Spigelia L. sect. Graciles (Loganiaceae) from northeastern Brazil - Macedo, Arthur; Pessoa, Edlley; Alves, Marccus (Phytotaxa, 2019)
A new species of Spigelia subg. Spigelia sect. Graciles, S. alborubra, is described and illustrated. It is known from Campos Rupestres and Caatinga s.s. in the states of Bahia and Pernambuco, Brazil. It is similar to S. pulchella, based on its exserted stigma and red corolla tube, but S. alborubra differs by its shorter corolla, with a constriction at the apex of the tube, whitish corolla lobes which open only at the apex, and by its inserted stamens. Based on the habit and on the shape of the corolla, it is superficially similar to other species of Spigelia subg. Spigelia sect. Graciles, such as S. gracilis, S. linarioides, S. schlechtendaliana and S. spartioides. However, the new species is easily distinguished from them by its salverform corolla and exserted stigma. According to the IUCN criteria, it is classified as Endangered (EN) due to its narrow distribution.